Pharmaceutical development of nanostructured vesicular hydrogel formulations of rifampicin for wound healing - Wallenwein, Chantal; Weigel, Verena; Hofhaus, Götz; Dhakal, Namrata; Schatton, Wolfgang; Gelperina, Svetlana; Groeber-Becker, Florian K.; Dressman, Jennifer; Wacker, Matthias G. (International journal of molecular sciences, 2022)
Chronic wounds exhibit elevated levels of inflammatory cytokines, resulting in the release of proteolytic enzymes which delay wound-healing processes. In recent years, rifampicin has gained significant attention in the treatment of chronic wounds due to an interesting combination of antibacterial and anti-inflammatory effects. Unfortunately, rifampicin is sensitive to hydrolysis and oxidation. As a result, no topical drug product for wound-healing applications has been approved. To address this medical need two nanostructured hydrogel formulations of rifampicin were developed. The liposomal vesicles were embedded into hydroxypropyl methylcellulose (HPMC) gel or a combination of hyaluronic acid and marine collagen. To protect rifampicin from degradation in aqueous environments, a freeze-drying method was developed. Before freeze-drying, two well-defined hydrogel preparations were obtained. After freeze-drying, the visual appearance, chemical stability, residual moisture content, and redispersion time of both preparations were within acceptable limits. However, the morphological characterization revealed an increase in the vesicle size for collagen-hyaluronic acid hydrogel. This was confirmed by subsequent release studies. Interactions of marine collagen with phosphatidylcholine were held responsible for this effect. The HPMC hydrogel formulation remained stable over 6 months of storage. Moving forward, this product fulfills all criteria to be evaluated in preclinical and clinical studies.